Unparalleled experiences of online medical education during Covid-19 pandemic - Mie, Mie Sein; Mya Sanda Khaing; Tin, Tin Thein; Fatimah Ahmedy (Universiti Malaysia Sabah, 2021)
COVID-19 pandemic in Malaysia has adversely affected the country in many aspects especially the economy and education sectors. Schools and universities alike are facing challenges in providing quality education to students. Many strategies have been recommended to improve the quality of online teaching to enhance students’ engagement in the teaching-learning processes. Massive Open Online Courses (MOOCs) are one of the alternative teaching strategies to advocate the students to access education remotely. It is time to take advantage of the uncertain period of COVID-19 into an opportunity to develop the MOOCs for the students.